Something in the Water: Hospital Responds to Water Crisis. (5th February 2018) - Redfern, Roberta; Micham, Jennifer; Daniels, Rebecca; Childers, Sue
Abstract: Early on August 2, 2014, in the city of Toledo, Ohio, a media alert informed the public that traces of microcystin, a hazardous toxin, had been detected in the drinking water. The warning stated that residents should not drink, boil, or even touch the contaminated water. A water crisis of this magnitude was recognized to pose a potentially serious and significant impact on patient care and safety in health care environments. ProMedica Toledo Hospital's Emergency Operation Plan addressed 3 critical issues: safe water availability, alternate cleaning solutions, and preparations for a prolonged crisis. This report details some of the lessons learned throughout the response to the crisis: particularly, because the impact was county-wide which affected other hospitals who used the same vendors, alternate water sources should have been secured in advance; the courier service was vital to delivery of supplies and moving equipment to alternate areas for sterilization processes; and finally, communication with staff and patients was jeopardized by external media outlets. Changes to the emergency plan considering these unanticipated aspects proved useful in a later incident and should be considered by all health care facilities as water emergency policies and procedures are created and reviewed. ( Disaster Med Public Health Preparedness . 2018;12:666–668)